Instrumental social support for the rural elderly: study of a rural block of a costal district of Odisha - Rath, Tuhinamsu; Panigrahi, Debabrata (International Journal Of Community Medicine And Public Health, 2017)
Background: The objectives of the study were to find out the social support extended to the rural elderly and to find out the trust worthy and long term support providers for them. Methods: An exploratory descriptive research design was adopted where 1088 subjects were interviewed (517 males and 571 females) with variables of age, sex and standard of living. As per the response to the questionnaires, the quality of social support for the rural elderly, the trustworthy and long term support providers were evaluated. Results: Out of 1088 elderly people participated in the study only 15% had someone trustworthy care providers where as 84.5% reported to have no trustworthy care providers. 34.4% of respondents had trust on their son as the old age care providers where as 30.4% had trust on their spouse. Similarly 94.4% reported to have long term care giver. 67.3% respondents were confident of receiving indefinite long term care where as 24.9% reported to have “now and then” care and 6.5% have short term care. The study also revealed that the middle aged (60-79 age groups) is less confident in securing instrumental social support than the very old. (80 above age group). It has also been observed that there is shrinkage in the number of long term care providers with increasing age. Conclusions: Instrumental social support plays a strategic role in the domain of health care, particularly in old age. The study found that rural elderly have less trustworthy care providers in old age. There is variation with regard to age, sex and standard of living. With regard to long term care, it is found that family comes to the centre stage where the core family members like son and spouse engineer the support service. Son is the most trusted care provider and males prefer spouse and females prefer their son as the trusted care provider in long term care. In order to enlarge the support system and raise the quality, support services need to be equipped. Instrumental social support can be both preventive of expansion of morbidity and protective of healthy ageing.